2014
DOI: 10.1638/2012-0281.1
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION AND CONTROL OF AN ATTACHING AND EFFACINGESCHERICHIA COLIOUTBREAK IN A COLONY OF CAPTIVE BUDGERIGARS (MELOPSITTACUS UNDULATUS)

Abstract: An increase in mortality in a captive flock of budgerigars (Melopsittacus undulatus) coincided with the isolation of attaching and effacing Escherichia coli from postmortem samples. Common histologic lesions included hepatitis, enteritis, and in one case attaching and effacing lesions along the intestinal tract. Retrospective review of necropsy records and increased sampling led to the identification of several cases of E. coli with the attaching and effacing (eae) virulence gene. Factors such as environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The latter may be at risk, when humans and other animals consume evolutionary ‘mismatched’ diets, i.e., diets they did not evolve to digest, absorb and utilise, and which typically come with novel sets of dietary toxins, antigens and microbial challenges. These factors are likely to contribute to the increased intestinal epithelial permeability, which has been implicated in the predisposition to intestinal inflammation and a number of gastrointestinal diseases in humans [ 43 ], zoo animals [ 45 ] and pets [ 46 ], laboratory rodents [ 47 ], domesticated livestock [ 48 ] and poultry [ 49 ]. Evidence is also growing that many wild animals are facing new dietary challenges resulting from global climate change [ 50 , 51 ].…”
Section: Perspectives and Significancementioning
confidence: 99%
“…The latter may be at risk, when humans and other animals consume evolutionary ‘mismatched’ diets, i.e., diets they did not evolve to digest, absorb and utilise, and which typically come with novel sets of dietary toxins, antigens and microbial challenges. These factors are likely to contribute to the increased intestinal epithelial permeability, which has been implicated in the predisposition to intestinal inflammation and a number of gastrointestinal diseases in humans [ 43 ], zoo animals [ 45 ] and pets [ 46 ], laboratory rodents [ 47 ], domesticated livestock [ 48 ] and poultry [ 49 ]. Evidence is also growing that many wild animals are facing new dietary challenges resulting from global climate change [ 50 , 51 ].…”
Section: Perspectives and Significancementioning
confidence: 99%
“…This study identified important DEC virulence genes (eaeA and bfpA) in Escherichia coli strains isolated from psittacine of illegal wildlife trade, which are important to diagnose the EPEC pathotype. Although these bacteria are recognized as important human pathogens (Peréz et al 2010, Gomes et al 2016, aEPEC have also been associated with increasing morbidity and mortality of Budgerigars (Seeley et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Avian colibacillosis aspects were described in a case report with a pet A. aestiva (Marietto-Gonçalves et al 2007), in which E. coli was isolated from several organs and lesions, which consisted of multiple granulomas and heterophilic infiltrate in lungs, congestion in kidneys, liver and brain, which are similar to the findings in this study. The most frequent lesions of colibacillosis are coagulative liver necrosis, aerossaculitis, granulomas, acute lung hemorrhage and congestion, enteritis with fusion of vili, epithelium hypertrophy and exfoliation, cellulitis with intense heterophilic infiltrate, multinuclear giant cells and fibrin-necrotic plaques; salpingitis with intense follicle necrosis and mixed infiltrate (Crespo et al 2001, Andrade et al 2006, Seeley et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent characteristics of avian salmonellosis are poor body condition, muscular atrophy, granulomas varying from multifocal to coalescent, transmural ulcerative necrosis of the gastrointestinal tract with clear presence of bacterial aggregation inside and outside the lesions, necrotizing hepatitis, interstitial pneumonia, myocarditis, epicarditis and necrotizing encephalitis (Madadgar et al 2009, Giovaninni et al 2012. In Australia, a flock of budgerigars with mortality caused by E. coli presented congestion and hemorrhage (Seeley et al 2014) as the main findings observed, similar to the results from this study, except the encephalitis present in different species of psittacine. The lesions caused by Salmonella Typhimurium in passerines in Switzerland had similar intensity to the ones caused by the strain in this study isolated from the A. aestiva, which was also sever necrotizing hepatitis (Giovaninni et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation